Inclusive digital connectivity for smart service value-chain: a systematic literature review - Rownak Tahmina; Mohammad Tarikul Islam, PhD; Abul Kalam Azad, PhD (Journal of Emerging Innovations in Engineering, 2026)
Smart services are vital for economic development and improved user experience, yet digital inequality continues to constrain their effective deployment in emerging economies. While prior studies emphasize smart technologies and digital connectivity, limited evidence explains how connectivity is transformed into value-creating smart services. This study addresses this gap by examining the relationship between digital connectivity and the smart service value chain through a digital inclusion lens. Using a qualitative approach, a systematic literature review guided by the PSALSAR framework is conducted. Academic and international regulatory sources are analysed through content analysis and pattern recognition. The findings show that political, economic, social, and technological (PEST) factors embedded in the connectivity ecosystem are critical to smart service value creation, with socio-economic factors exerting greater influence than technology alone. The study informs conceptual development, service design, and digital policy reform for inclusive smart service ecosystems.